Small ruminant breeding programs focusing on centralized nucleus and crossbreeding have failed in Ethiopia and need re-think - Haile, Aynalem; Getachew, Tesfaye; Belay, Berhanu; Rekik, Mourad; Legesse, Getachew; Solomon, Dawit; Rischkowsky, Barbara (International Center for Agricultural Research in the Dry Areas, 2023)
Small ruminant breeding programs focusing on centralized nucleus and crossbreeding have failed in Ethiopia and need to be re-think.